Pengaruh Penggunaan Abu Cangkang Telur Sebagai Pengganti Sebagian Filler Terhadap Sifat Campuran Aspal Beton (AC-WC) Dengan Perendaman Berulang - Hurul Ainun Parenrengi; Abdul Rahim Nurdin; Tamrin Mallawangeng (Jurnal Penelitian Teknik Sipil Konsolidasi, 2026)
Asphalt Concrete – Wearing Course is a layer designed to withstand traffic loads and protect the underlying layers from damage caused by environmental factors such as water and temperature. This research aims to analyze the effect of partial replacement of eggshell ash filler on the properties of AC-WC mixtures with soaking variations. This study used 0%, 20%, 40%, 60%, 80%, and 100% eggshell ash. The sample preparation consisted of no soaking, 3 days of soaking, and  9 days of soaking (the sample is soaked for 24 hours then removed and allowed to stand at room temperature for 24 hours; this is repeated 3 times and 9 times). The tested things were stability, flow, VMA, VFB, VIM, content weight, and 200-pass ratio. The sample testing used the Marshall tool. The test results showed that the best variation was 60% eggshell: 40% cement with 3 days of soaking.